Pengaruh Transformasi Digital, Motivasi Kerja dan Kepemimpinan Transformasional terhadap Kinerja Pegawai pada Kantor Dinas Pertanian Kabupaten Asahan - Arjuna Arjuna; Hadi Suriono (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The rapid development of digital technology has encouraged public sector organizations to improve employee performance through digital transformation, work motivation, and transformational leadership. However, the implementation of these aspects in government institutions is often not fully optimized, resulting in variations in employee performance. This study aims to analyze the effect of digital transformation, work motivation, and transformational leadership on employee performance at the Department of Agriculture of Asahan Regency. The research employed a quantitative approach with a descriptive design. The population consisted of 31 employees, all of whom were selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 26. The findings indicate that partially, digital transformation and work motivation did not have a significant effect on employee performance. In contrast, transformational leadership showed a positive and significant influence on employee performance. Simultaneously, the three independent variables significantly affected employee performance. The coefficient of determination demonstrated that employee performance was strongly influenced by digital transformation, work motivation, and transformational leadership. These findings highlight the importance of transformational leadership in strengthening employee performance within public sector organizations undergoing organizational change.